Effects of dietary inorganic nitrate on blood pressure during and post-exercise recovery: A systematic review and meta-analysis of randomized placebo-controlled trials - Benjamim, Cicero Jonas R.; Lopes da Silva, Leonardo S.; Valenti, Vitor E. [UNESP]; Gonçalves, Leonardo S.; Porto, Andrey A. [UNESP]; Tasinafo Júnior, Márcio Fernando; Walhin, Jean-Philippe; Garner, David M.; Gualano, Bruno; Bueno Júnior, Carlos R. (Elsevier, 2024)
Objectives: A systematic review with meta-analysis was completed to study the effects of dietary inorganic nitrate (NO3−) oral ingestion from vegetables and salts on blood pressure responses during and following exercise. Background: NO3− is a hypotensive agent with the potential to reduce blood pressure peaks during exercise and amplify exercise-induced hypotensive effects. Several randomized and controlled trials have investigated the effects of NO3− on hemodynamic responses to physical exercise, however this still has yet to be studied systematically. Methods: The searches were conducted on EMBASE, Medline, and SPORTSDiscus databases. The study included masked randomized controlled trials (RCTs) with participants ≥18 years old. The NO3−intervention group received at least 50 mg NO3−/day with similar sources amid NO3− and placebo conditions. Included studies reported systolic blood pressure (SBP) or diastolic blood pressure (DBP) values during or following exercise performance. Results: 1903 studies were identified, and twenty-six achieved the inclusion criteria. NO3− daily dosages ranged from 90 to 800 mg/day. Throughout exercise, SBP had smaller increases in the NO3− group (−2.81 mmHg (95%CI: −5.20 to −0.41), p=0.02. DBP demonstrated lower values in the NO3− group (−2.41 mmHg (95%CI: −4.02 to −0.79), p=0.003. In the post-exercise group, the NO3− group presented lower SBP values (−3.53 mmHg (95%CI: −5.65 to 1.41), p=0.001, while no changes were identified in DBP values between NO3− and placebo groups (p=0.31). Subgroup meta-analysis revealed that SBP baseline values, exercise type, duration of NO3− ingestion, and its dosages mediated blood pressure responses during and following exercise. Conclusions: NO3− ingestion prior to exercise attenuated the increases in SBP and DBP during exercise, and increased the decline in SBP after exercise. These results are dependent on factors that moderate the blood pressure responses (e.g., health status, type of exercise, resting blood pressure values).
Keywords: Cardiovascular responses to exercise; Hemodynamic monitoring; Nitric oxide; Nitrite; Post-exercise hypotension